Analisis Optimalisasi Pemanfaatan Aset Tetap dalam Meningkatkan Pendapatan pada UIN Imam Bonjol Padang - Repwita, Yena; Suhairi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to assess the optimization of fixed asset utilization in increasing revenue at UIN Imam Bonjol Padang, evaluate the implementation of five dimensions of accountability, and identify inhibiting factors and underutilized assets with economic potential. A qualitative case study approach was employed, supported by quantitative data from asset inventory results. Data were collected through in-depth interviews, observation, and documentation. The analysis refers to five dimensions of accountability: legal, performance/process, program, policy, and financial. The findings indicate that asset utilization remains suboptimal and the implementation of accountability is not yet fully effective. Key barriers include the absence of a strategic roadmap, limited human resources, weak information systems, and inflexible policy frameworks. These results highlight the need for improved asset governance based on accountability principles to enhance institutional efficiency, transparency, and financial sustainability.